Karl Marx's Das Kapital explained - Lim, Seungsoo, 1975- (Algora Publishing, 2019)
"This is a lucid step-by-step guide to Karl Marx's Capital for all the readers of the world. Its treatment of the content of Capital pivots on the classroom exchanges between the lecturer and his students"--